Removal of pollutants from wastewater using coffee waste as adsorbent: A review. (October 2022) - Kang, Le-Le; Zeng, Ya-Nan; Wang, Yi-Tong; Li, Jun-Guo; Wang, Fu-Ping; Wang, Ya-Jun; Yu, Qing; Wang, Xiao-Man; Ji, Rui; Gao, Di; Fang, Zhen
Abstract: The problem of water pollution is becoming more and more serious, and many pollutants are carcinogenic and pose a serious threat to global sustainable and green development. Adsorption is a promising wastewater treatment process, and agricultural wastes as adsorbents are popular in various wastewater treatments. The world produces >6 million tons of coffee crops annually, and every ton of coffee generates 0.68 tons of coffee waste. Because coffee waste (i) has a surface with a porous structure, (ii) contains cellulose, hemicellulose, and lignin structure that can provide abundant functional groups, and (iii) is recyclable to make it have remarkable performance in wastewater treatment, and its reuse not only saves processing costs but also contributes to the sustainable development of the environment. This review focuses on the application of coffee waste sorbents in the removal of pollutants from wastewater. The methods and advantages and disadvantages of physical pretreatment, acid pretreatment, alkali pretreatment, and magnetic pretreatment of coffee waste were reviewed. Four types of adsorption experiments including adsorption experiments, adsorption kinetics, adsorption isotherms, and adsorption thermodynamics of heavy metals, dyes, antibiotics, and other organic pollutants removal efficiency are investigated and their adsorption potential is discussed. Finally, a brief conclusion and future perspective for coffee waste that applies to wastewater treatment are provided. Graphical abstract: The coffee waste without any pretreatment or after physical pretreatment, acid-base pretreatment and magnetic pretreatment can effectively remove heavy metals, dyes, antibiotics and other pollutants in wastewater. Unlabelled Image Highlights: Adsorption capacity of the adsorbent was analyzed according to adsorption experiments, isotherms, kinetics. Pretreatment methods of coffee waste and its advantages and disadvantages were reviewed. Langmuir and pseudo second order were the most suitable models for coffee waste adsorption. Reusable adsorbents were beneficial to sustainable development. Gap analysis and future prospects of coffee waste as adsorbents were discussed.